Treatment of Class II malocclusion with deep overbite - Oliveira, Silvio Rosan (2008)
A case report of a 10 years and 11 months patient indicated for treatment of a skeletal Class II due to a maxillary protrusion and deep overbite. The patient expressed great worry related to his self-image because his large overjet resulting in soft tissue profile imbalance due to 6mm of overjet and 8mm of overbite. Therapeutic procedures are described for promotion the facial and cephalometric alterations caused by the Kloehn extra-oral traction and J Hook, moreover the four premolars extraction used to correct the Class II deep overbite malocclusion.